Radiative Heat Transfer Flow of Micropolar Fluid with Variable Heat Flux in a Porous Medium - Rahman, M. M. M.; Sultana, T. (Nonlinear Analysis: Modelling and Control, 2008)
A two-dimensional steady convective flow of a micropolar fluid past a vertical porous flat plate in the presence of radiation with variable heat flux has been analyzed numerically. Using Darcy-Forchheimer model the corresponding momentum, microrotation and energy equations have been solved numerically. The local similarity solutions for the flow, microrotation and heat transfer characteristics are illustrated graphically for various material parameters. The effects of the pertinent parameters on the local skin friction coefficient, plate couple stress and the heat transfer are also calculated. It was shown that large Darcy parameter leads to decrease the velocity while it increases the angular velocity as well as temperature of the micropolar fluids. The rate of heat transfer in weakly concentrated micropolar fluids is higher than strongly concentrated micropolar fluids.